Using a customized board game to improve English learning’s experience and effectiveness - Ounu Zakiy Sukaton; Wawan Eko Yulianto; Melany Melany; Lilis Lestari Wilujeng (University of Merdeka Malang, 2023)
English language learning is an integral part of basic education in Indonesia today. However, not all students have equal opportunities to learn English. Elementary school children in Kucur village, in particular, are among those who lack sufficient access to learning English outside the classroom due to their family circumstances. Fortunately, there is a Learning Center called Cakrawangsa managed by the local youth organization (Karang Taruna) in Krajan hamlet, Kucur village. This center provides educational assistance to students. However, the center lacks permanent human resources to support students in learning English. In 2021, the community engagement team from Ma Chung University conducted once-a-week fun English learning sessions. Based on the evaluation results of the program, the participants greatly enjoyed the fun learning approach delivered by the Ma Chung University community engagement team. However, some students still struggled to memorize English vocabulary and pronounce it accurately. Therefore, the proposing team suggests a supplementary English learning program using an enjoyable method that has the potential to enhance vocabulary mastery. Based on conducted studies, the proposing team has developed a relevant board game tailored to the students' environment as an engaging and effective tool to support English language teaching.